Microencapsulation of Piscirickettsia salmonis Antigens for Fish Oral Immunization: Optimization and Stability Studies - Sotomayor-Gerding, Daniela (Polymers, 2024)
The development of fish oral vaccines is of great interest to the aquaculture industry due to the possibility of rapid vaccination of a large number of animals at reduced cost. In a previous study, we evaluated the effect of alginate-encapsulated Piscirickettsia salmonis antigens (AEPSA) incorporated in feed, effectively enhancing the immune response in Atlantic salmon (Salmo salar). In this study, we seek to characterize AEPSA produced by ionic gelation using an aerodynamically assisted jetting (AAJ) system, to optimize microencapsulation efficiency (EE%), to assess microparticle stability against environmental (pH, salinity and temperature) and gastrointestinal conditions, and to evaluate microparticle incorporation in fish feed pellets through micro-CT-scanning. The AAJ system was effective in obtaining small microparticles (d < 20 mu m) with a high EE% (97.92%). Environmental conditions (pH, salinity and temperature) generated instability in the microparticles, triggering protein release. 62.42% of the protein content was delivered at the intestinal level after in vitro digestion. Finally, micro-CT-scanning images confirmed microparticle incorporation in fish feed pellets. In conclusion, the AAJ system is effective at encapsulating P. salmonis antigens in alginate with a high EE% and a size small enough to be incorporated in fish feed and produce an oral vaccine.